Pelatihan Menyusun Bukti dengan Sketchpad Bagi Guru Matematika SMA di Kota Prabumulih - Kurniadi, Elika; Hartono, Yusuf; Retna Safitri, Erna; Siska Utari, Rahma (Jurnal SOLMA, 2025)
Background: This Community Service (PkM) activity aims to enhance the reasoning and proof competencies of Mathematics teachers in Prabumulih City through training in the use of Geometer's Sketchpad software. An initial survey identified that many teachers had a negative perception of mathematical proof, felt difficulty in constructing proofs, and lacked the use of technology in teaching. Methods: The training was conducted in a hybrid format, combining face-to-face and online methods, with an emphasis on interactive approaches. Result: The results showed a significant increase in teachers' understanding of mathematical concepts and their ability to construct proofs. Approximately 90% of teachers stated that evidence-based learning improves the quality of education. Although progress was made, additional training is still needed for some teachers who struggled with using Geometer's Sketchpad. These findings highlight the importance of ongoing support and further training to sustain teachers' competency development, as well as encourage the application of more innovative teaching methods. Conclusion: Thus, this activity is expected to improve the quality of mathematics education in schools and prepare students to face academic challenges in the future.